Performance and cost analysis of diesel engine with different mixing ratio of raw vegetable oil and diesel fuel - Uddin, Md. Nasir; Rashid, Muhammad Mahbubur; Nithe, N. A.; Rony, J. I. (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The main focus of this study is to performance test of a one cylinder four stroke ZS1115 diesel engine running by diesel fuel, raw preheated soybean oil fuel, mixture of 80% diesel fuel & 20% raw preheated soybean oil fuel, mixture of 50% diesel fuel & 50% raw preheated soybean oil fuel, mixture of 30% diesel fuel & 70% raw preheated soybean oil fuel and mixture of 20% diesel fuel & 80% raw preheated soybean oil fuel, and finally compare the performance among them. The mixture of 50% diesel fuel & 50% raw preheated soybean oil fuel performed better than others with respect to the graph brake thermal efficiency vs. brake mean effective pressure and the graph of brake specific fuel consumption vs. brake mean effective pressure. This study also present the cost required to produce per kW power developed in TK. The mixture of 80% diesel fuel & 20% raw preheated soybean oil fuel shows the lowest cost and raw preheated soybean oil fuel shows the highest cost.